Level of Mastery of Arabic Language Communication Skills among Students in Religious Secondary Schools in Kuala Muda District, Kedah Darul Aman - Mohd Sofar, Noor Amrina Rosyada (SIBAWAYH Arabic Language and Education, 2023)
Communication is very important in ensuring that information can be delivered accurately. However, communication skills in Arabic among students is still an issue among scholars. Therefore, this study examines the level of mastery of Arabic language communication skills among students in one of the religious secondary schools in Kuala Muda district, Kedah. This study examines from the aspect of students’ motivation in communicating in Arabic, the factors that cause lack of vocabulary, the role of teachers in improving students’ communication skills. This study is a quantitative study, using a questionnaire as the main instrument. The study involved 80 participants selected through simple random sampling. Data were analyzed descriptively using IBM SPSS software. The results of the study show that motivation plays an important role in students’ efforts to learn Arabic, with a strong emphasis on memorizing vocabulary and a positive attitude towards the language. However, challenges such as lack of practice in daily life and fear of grammatical mistakes hinder students’ communication ability. Second, the study identified factors that influence the lack of Arabic vocabulary, with the need for teachers to stimulate students’ interest in communicating in Arabic being the most significant. This shows that effective teaching strategies, including creative and engaging approaches, are important in promoting language learning. This study contributes to the existing literature on the level of Arabic language communication among students and reveals new findings from the students’ point of view related to difficulties in communicating in Arabic.